Computer Program for Primer Design for Loop-Mediated Isothermal Amplification (LAMP) - Akhmetzianov, L. U. (Advanced engineering research (Rostov-na-Donu, Russia), 2024)
Introduction. To date, numerous methods of nucleic acid amplification have been proposed, and each method has a number of advantages and disadvantages. One of the most popular methods is Loop-mediated isothermal AMPlification (LAMP). Unlike thermocyclic reactions, such as PCR (polymerase chain reaction), which require three temperature changes and expensive equipment, in LAMP, the entire reaction takes place at one and the same temperature and at the maximum rate possible. An important component of LAMP-amplification is primers (usually 20–25 nucleotides), which need to be matched to a specific part of the nucleotide sequence. It is known that DNA sequence contains four nucleotides: A — adenine and T — thymine, G — guanine and C — cytosine. There is a huge variety of permutations of these nucleotides, and it is practically impossible to analyze such a large amount of data manually. Therefore, there is a need to use modern computer technologies. More than 150 computer programs have been proposed for the design of PCR primers, while for LAMP-primers there are less than 10 of them, and each of them has a number of drawbacks, e.g., in terms of the length of the analyzed site. Therefore, this work is aimed at developing a new domestic computer program for the design of specific primers for LAMP. Materials and Methods. The primer search algorithm was based on a linear search for a substring in a string, taking into account the criteria of primer selection for LAMP. The program complex of LAMP-primer design was implemented in Python programming language. The bioPython library was used to work with various DNA and RNA, and the Qt framework was used to develop the interface. Results. A modification of the direct sampling method using a stencil approach was proposed, taking into account the GC composition and annealing temperature of primers depending on their structure. A software package with a friendly interface was developed. It took into account the design criteria of primers: certificates of registration of computer programs (LAMPrimers iQ No. 2022617417 dated April 20, 2022, LAMPrimers iQ_loop No. 2023662840 dated June 14, 2023) were received. The program is in the public domain at https://github.com/Restily/LAMPrimers-iQ Discussion and Conclusion. The developed software packages can be used for research and analysis in molecular biology and genetics, to create diagnostic test systems that provide high sensitivity and reliability of detection of specific DNA and RNA. The software packages can be used in research institutes and laboratories engaged in the amplification of nucleic acids. The results of evaluating the selected sets of primers for the LAMP reaction were tested, and the effectiveness of working sets using the LAMPrimers iQ program was experimentally proven by the example of the detection of genetic material of the SARS-CoV-2 coronavirus.